PENURUNAN KADAR COD DAN BOD PADA LIMBAH CAIR KIMIA LABORATORIUM POLTEKKES KEMENKES BENGKULU DENGAN METODE BIOFILTER - Fandini, Mutia Ade (JURNAL MEDIA KESEHATAN, 2015)
Laboratory waste is one of the waste in a small scope that tends contained manyheavy metals and organic materials therein. The nature of the waste is very dangerous andtoxic may not directly discharged into the environment. One of the sewage treatment by usingthe method biofilter. The purpose of this research is to reduce levels of COD and BODeffluent MoH Bengkulu polytechnic chemistry laboratory methods biofilter. Type of quasiexperimental study with pre-post study design test. Waste derived from laboratory chemicalwaste. Measure the COD and BOD levels before and after treatment biofilter with fiverepetitions. Analyzed by univariate and bivariate. Given the results of research based on theanalysis of univariate no reduction in COD levels by an average of 5.448% and the percentagereduction in BOD levels decrease with the average percentage of 3.928% decline. Results ofbivariate analysis test t-Test that there are differences in the levels of COD before and aftertreatment with 0.006 significance and there are differences in levels of BOD before and aftertreatment with 0.003 significance